Effects of land use, meteorology, and hydrology on nutrients, biochemical indexes, and heavy metals in Qingjiang River Basin, China. (10th October 2022) - Zhou, Hongying; Rao, Ke; Yao, Maojun; Xiong, Ying; Wang, Yi; Yin, Yinghua
Abstract: Land use, meteorology, and hydrology can critically influence the water quality in rivers. However, few studies have comprehensively assessed the influences of these factors on nutrients, biochemical indexes, and heavy metals. In this study, water samples were collected monthly from 10 sampling sites in a headwater region of Qingjiang River Basin from 2016 to 2020. Nutrients, biochemical indexes, and heavy metals were analyzed to explore their spatial-temporal distributions, identify the significance of pollution types, and study the effects of land use, meteorology, and hydrology on water quality. The results indicated that there were significant spatial differences for nutrients and biochemical indexes, while significant seasonal differences for heavy metals in the study area. The seasonal Manne-Kendall test suggested there were increasing trends of nutrients, while relatively stable trends of biochemical indexes and decreasing trends of heavy metals during the study period. The principal component analysis showed nutrients were the key pollution type in urban areas, while biochemical indexes were the key pollution type near the dam. The redundant analysis indicated that explained rates of land use compositions on the water quality were in the order: riparian buffer zones > sub-watershed zones > upstream circle buffer zones > Thiessen polygons zones. The explained rates were larger during the wet season than the dry season except for upstream circle buffer zones, which might be the result of diverse influences of the precipitation on different land use types. The classification and regression tree model showed nutrients were more affected by urban compositions, and biochemical indexes were influenced by both the precipitation and agriculture compositions. The nonparametric change point analysis further indicated total nitrogen, total phosphorus, and potassium permanganate index would increase abruptly when urban compositions were above 3.7%, 9.94%, and agriculture compositions were above 36.55% respectively at the 900 m riparian buffer zone. Cu, Pb, and As, however, were more associated with the precipitation, and they might decrease abruptly when the precipitation was above 4.68 mm. The results highlighted the inconsistent role of land use, meteorology, and hydrology on different water quality indexes, which can provide the scientific basis for the management of the water environment in rivers. Graphical abstract: Image 1 Highlights: Spatial-temporal dynamics of nutrient, biochemical and heavy metal were analyzed. The importance of pollution types changed with space variation. Effects of land use on water quality were dependent on spatial scales and seasons. The most influencing factor changed with different water quality indexes. The change points and their uncertainties of key factors were examined.